Green nanomaterials in halal applications - Azmi, Nor Azrini Nadiha; Mohd Noor, Najihah; Elgharbawy, Amal A.M.; Moniruzzaman, Muhammad; Kaharudin, Norsavina (Springer Singapore, 2024)
The field of nanotechnology places particular emphasis on the utilisation of specialised materials or structures that exist at the nanoscale, a size range that is typically defined as being 100 nm or smaller. In recent decades, there has been significant development in the fields of nanotechnology and nanomaterials. The materials that have been engineered to a diminutive scale are intriguing due to their minute dimensions and augmented surface-to-volume ratio. The integration of green chemistry into the field of nanotechnology has presented a promising outlook for its future. The field of green nanotechnology involves the synthesis of nanomaterials through the process of biosynthesis, which is widely recognised for its eco-friendliness, efficiency, and scalability. In recent years, there has been significant research conducted on green nanomaterials, particularly in the biomedical sector, as a result of these various contributing factors. Green nanomaterials find their primary applications in three distinct categories, namely drug delivery, therapy, and diagnosis. Nanomaterials are primarily utilised in the domains of bioimaging and biosensors for diagnostic purposes, whereas their applications in cancer treatment and antibacterial agents are predominantly geared towards therapeutic interventions. Due to the fact that a majority of biological processes occur at the nanoscale level, nanomaterials are highly compatible with biomedical equipment. Thus, it is a domain worth investigating in the context of halal applications, specifically pertaining to the areas of detection and authentication.